1989
DOI: 10.1021/j100355a048
|View full text |Cite
|
Sign up to set email alerts
|

Benzene carbon-deuterium bond activation by free vanadium cluster cations

Abstract: aqueous phase on the organic liquid, however, has not been commented upon nor rigorously assessed. To a first approximation, one assumes that the "interfacial" organic liquid behavior parallels that of the bulk phase. How do these observations compare to the phospholipid bilayer-water interface?Consider first the acyl chain region. In the center of a bilayer, e.g., composed of DMPC, the viscosity has been determined to be about 1.5 P, a value about 200 times greater than that of water and equivalent (approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
64
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 1 publication
7
64
0
Order By: Relevance
“…13,[26][27][28][29][30][31][32][33][34][35] The reaction rate towards H 2 and N 2 is found to correlate with the electronic properties as expressed, e.g., by an ͑effective͒ ionization potential of the cluster. 13,34 The presence of isomers for several cationic and neutral clusters in the size range between 9-20 atoms has been observed in reactivity studies [30][31][32][33][34][35] but also spectroscopically. 12,14,15 In electric deflection experiments on neutral niobium clusters a strong variation in the per-atom polarizability has been found and it has been suggested that this is related to large size-dependent variations in the electronic or geometric structures.…”
Section: Introductionmentioning
confidence: 99%
“…13,[26][27][28][29][30][31][32][33][34][35] The reaction rate towards H 2 and N 2 is found to correlate with the electronic properties as expressed, e.g., by an ͑effective͒ ionization potential of the cluster. 13,34 The presence of isomers for several cationic and neutral clusters in the size range between 9-20 atoms has been observed in reactivity studies [30][31][32][33][34][35] but also spectroscopically. 12,14,15 In electric deflection experiments on neutral niobium clusters a strong variation in the per-atom polarizability has been found and it has been suggested that this is related to large size-dependent variations in the electronic or geometric structures.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] The rapid development of experimental techniques in recent years has made it possible both to obtain size-controlled transition metal clusters and to study their reactivity against chemisorption processes. [6][7][8][9] Methods for studying properties and behavior of clusters have been developed, and a review on computational studies of clusters has been written by Freeman and Doll. 10 There have been many studies on nickel clusters using various methods of exploring the potential energy surfaces ͑PES͒.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] For example, oxygen adsorption reactivities of Au anion clusters exhibit an even/odd alternation, i.e., Au anion clusters with even numbered gold atoms are active for oxygen adsorption, whereas odd-numbered clusters are inert. 5 Rates of chemisorption for H 2 , D 2 , and N 2 on Fe n ͑Refs.…”
Section: Introductionmentioning
confidence: 99%
“…5 Rates of chemisorption for H 2 , D 2 , and N 2 on Fe n ͑Refs. 8 and 9͒ and Nb n clusters, [10][11][12][13][14] and CO on different metal clusters 15 vary by several orders of magnitudes as a function of n. Tungsten clusters (W n , nϭnumber of atoms͒ with nϽ15 show relatively low reactivities toward nitrogen adsorption, whereas a sharp jump of the reactivity is detected for n ϭ15 at liquid-nitrogen temperature as well as room temperature. 6,7 In many cases, correlations between electronic structures ͑for example, ionization potentials͒ and chemisorption reactivities of metal clusters have been found.…”
Section: Introductionmentioning
confidence: 99%